If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying U = 7x + 6b + -5 + 2x + -6b + 4 Reorder the terms: U = -5 + 4 + 6b + -6b + 7x + 2x Combine like terms: -5 + 4 = -1 U = -1 + 6b + -6b + 7x + 2x Combine like terms: 6b + -6b = 0 U = -1 + 0 + 7x + 2x U = -1 + 7x + 2x Combine like terms: 7x + 2x = 9x U = -1 + 9x Solving U = -1 + 9x Solving for variable 'U'. Move all terms containing U to the left, all other terms to the right. Simplifying U = -1 + 9x
| 4y=120 | | (p^5/p^3)^6 | | 12m=9 | | 3x^2+6y^2=18 | | 5x-11=2(x+2) | | J=11-2.5(1.56) | | Z+-4x=2y | | y^3+2x=x-1 | | (8+2i)(5-9i)= | | -36+4x=12 | | 2x+4y-1=3+y | | 8-8x20/20 | | f(x+8)=2x-4 | | x^2+lnx-1=0 | | 15+5x=40 | | (7/(3a))/(2/5) | | 2x^-5/3y^0 | | (7/(3a))/(2.5) | | x=1/50 | | -(-8)/(-8)-3 | | 2/5x30=-50 | | 2x=1/25 | | 8x+3=3x+9 | | 3(2x+8)=15 | | cosx/3=0 | | -3x+14=23 | | R=-4x-9z+5z-9x+3x-8z | | x*2=1/25 | | 9y^2+1=6x | | (10x^6)(5x^2)= | | A=-7x+3y-7y+8x-6x+9y | | 15x^2+x^3=0 |